Winner Semiconductors The Ultimate Dielectrics is ... Nothing. - Adee, S.
This paper presents IBM air gap technology, in which wires are placed in vacuum to speed chips and save power.
Keywords: Air gap technology; Dielectric isolation; Microprocessor chips